2020
DOI: 10.1177/0300060520934288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baicalin on gestational hypertension-induced vascular endothelial cell damage

Abstract: Objective Baicalin is a compound extracted from the dried root of Scutellaria baicalensis Georgi. Studies have shown that baicalin has a protective effect on vascular endothelial cells, but whether baicalin could alleviate ascular endothelial cell damage in pregnancy-induced hypertensive patients remains unknown. Materials and methods We established a hypertensive pregnant rat model to study vascular endothelial injury during pregnancy-induced hypertension. Plasma epoprostenol (PGI-2), thromboxane A2 (Txa-2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Pregnancy hypertension is a group of diseases associated with gestational hypertension, preeclampsia, and eclampsia; chronic hypertension is associated with complications of preeclampsia; pregnancy with complications of hypertension will increase with gestational age. Damage to pregnant women is shown in Figure 1 ; the effect can be reversible [ 1 ]. Hypertensive disease during pregnancy has always been a disease of great concern to obstetric workers, and it is a major risk factor for maternal and perinatal life and death.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy hypertension is a group of diseases associated with gestational hypertension, preeclampsia, and eclampsia; chronic hypertension is associated with complications of preeclampsia; pregnancy with complications of hypertension will increase with gestational age. Damage to pregnant women is shown in Figure 1 ; the effect can be reversible [ 1 ]. Hypertensive disease during pregnancy has always been a disease of great concern to obstetric workers, and it is a major risk factor for maternal and perinatal life and death.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, it was difficult to divide the patients into groups, as 11 patients were diagnosed with GH and PE simultaneously. Further, PE, GH, and GDM are all associated with endothelial damage (20)(21)(22), and platelets increase destruction and production as a result of larger and younger platelets being released into the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Citri Reticulatae Pericarpium has the functions of invigorating the spleen and regulating the stomach. The whole prescription can reinforce qi, strengthen the spleen, calm the liver, and reinforce the kidney [ 23 28 ]. Recent research has reported that Atractylodes macrocephala and Poria cocos can enhance human immunity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%